Effect of Operational Costs on Net Profit in Indonesian Food and Beverage Manufacturing Firms, 2022–2024 period - Risya Artika; Indayani Indayani; Nur Qamariah S; Aswar Rahmat (Pustaka Digital Indonesia, 2026)
The urgency of this research lies in providing empirical evidence on how operational costs affect net profit in Indonesian food and beverage manufacturing firms during the 2022–2024 period, offering valuable insights for improving efficiency and profitability. The research is motivated by the growing importance of operational cost efficiency in maintaining profitability and business sustainability amid increasing industry competition. Using a quantitative approach and secondary data obtained from the Indonesia Stock Exchange, the study analyzed 159 financial statements from 53 companies selected through purposive sampling. Data were processed using simple linear regression with SPSS version 25. The results indicate that operational costs have a positive and significant effect on net profit. The positive regression coefficient suggests that higher operational costs are associated with increased net profit, reflecting productive business activities that support revenue growth. The t-test confirms the significance of this relationship, with the calculated t-value exceeding the critical value and a significance level below 0.05. In addition, the coefficient of determination (R²) of 0.854 shows that 85.4% of the variation in net profit can be explained by operational costs, while the remaining 14.6% is influenced by other factors not included in the model. These findings provide empirical evidence on the importance of operational cost management in improving financial performance and profitability. The study implies that companies should optimize the allocation and utilization of operational costs to enhance efficiency and support profit growth. Overall, operational costs play a substantial role in determining net profit among food and beverage manufacturing firms in Indonesia.